PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 017 BUKIT LIPAI - Dwi Rastuti Handayani; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Class Action Research aims to improve learning outcomes IPS through cooperative learning model examples of non examples in Class IV SD Negeri 017 Bukit Lipai which took place April 15 through May 11 2016. Latar the back of this study is the low value of this IPS caused less precise methods of learning, in presenting the material teachers only use the lecture method, question and answer so that students are less excited not attract even the students tend to be passive in the course. It can be seen from the foregoing data only scored an average 67.05 completeness only reached 58.82%. While the minimum completeness criteria assigned 70. To overcome these problems, the teacher tries to make a new breakthrough, the teacher made repairs learning in order to improve student learning outcomes, one model of learning that are examples of cooperative non examples. This classroom action research conducted in two cycles, the first cycle was held two meetings and one daily tests, and a second cycle also held two meetings and one daily tests. The results showed an increase in student learning outcomes, in the first cycle absorption students with an average of 77.64%, while in the second cycle absorption reached 79.11% and classical learning completeness individually has been reached. I cycle students completeness 14 (82.35%), while in the second cycle 17 (100%). Student activity increased in the first cycle an average of 80% while in the second cycle was 86%. The activities of teachers also increased in the first cycle the average reached 85% and the second cycle reaches 88%.Keywords: Examples of non examples, learning outcomes IPS.